Primary progressive aphasia - V. A. Mikhailov; Yu. V. Kotsiubinskaya; N. Yu. Safonova; N. I. Ananieva; I. K. Stulov (Неврология, нейропсихиатрия, психосоматика)
Primary progressive aphasia (PPA) is a heterogeneous group of neurodegenerative diseases related to focal degenerations of the brain and mainly manifested by a gradual loss of speech functions. This symptom is characterized by specific speech disorders. The article presents the etiopathogenic features of PPA, systematizes the clinical criteria for its diagnosis, and describes the modern neuroimaging characteristics of different types of PPA. The proposed PPA severity point scale allows clinicians to record the very early manifestations of aphasia. Modified scales, such as the Frontal Behavioral Inventory (FBI-mod) and the Clinical Dementia Rating (CDR), are also important for specifying the type of PPA.